ANALISA PERILAKU KONSUMTIF DAN DAYA BELI KONSUMEN TERHADAP PENJUALAN ONLINE SELAMA MASA PANDEMI COVID -19 - Ricky Atmaja; Mira Maryani (Program Studi Magister Manajemen Universitas Advent Indonesia, 2021)
The prolonged Covid-19 pandemic has an impact on people's economic activities, there is a shift in transactions, changes in consumer behavior and purchasing power of the community, this is due to government policies in restricting community activities. This study aims to measure consumptive behavior and purchasing power towards online sales during the Covid-19 pandemic. The population of the study was respondents who had online shopping experience and a sample of 50 respondents were taken with a simple random sampling technique. The research method used is quantitative descriptive method, data collection technique with questionnaire dissemination, before the data is analyzed research instrument first conducted validation test and classic assumption test. The research hypothesis was tested partially and simultaneously with a signification rate of 5%. The results showed that consumptive behavior (X1) affects online sales and purchasing power (X2) negatively affects online sales.